Direct Composite Resin Restoration of Anterior Maxillary Teeth and Esthetic Smile Design: A Case Report - Widya Nugrohowati, Christina; Hadriyanto, Wignyo; Nugraheni, Tunjung (Journal of Dentistry Indonesia, 2020)
Dental esthetic complex involves more than one caries with malformed shape and malposition. Dental trauma most commonly affects maxillary anterior teeth, and subsequently affects the esthetics, functions, and psychological well-being of the individual. Composite resins have become an integral part of contemporary restorative and minimally invasive dentistry. Objective: To summarize the successful use of direct composite resin restoration in the management of a 29-year old male patient. Case Report: A 29-year old male patient presenting with multiple secondary caries and crown fractures in the anterior maxillary teeth, resulting in an unaesthetic smile. Comprehensive esthetic dental treatment was carried out. The patient was highly satisfied with the results even after eleven months of follow-up. Conclusion: restorative success with composite resins, the dental treatment plan should be carefully executed with attention to factors such as dental convexities and contours, re‑establishment of function, and esthetics. Smile design should always be a multifactorial decision-making process that allows the clinician to treat patients with an individualized and interdisciplinary approach.